Implementation of Immigration Supervision Policy on Foreign Citizens' Residence Permits at the Class I TPI Padang Immigration Office - Revi Marizska; Rahmadani Yusran (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The implementation of immigration supervision policies for foreign nationals (WNA) requires organizational capacity capable of integrating various resources to ensure the effectiveness of supervision. This study aims to analyze the implementation of immigration supervision policies for foreign nationals (WNA) at the Class I TPI Padang Immigration Office by identifying factors that support and hinder policy implementation. The study used a qualitative approach with descriptive methods. Data were obtained through interviews, observations, and documentation, then analyzed using the Miles, Huberman, and Saldana model with the George C. Edwards III policy implementation framework covering communication, resources, disposition, and bureaucratic structure. The study shows that policy implementation has been carried out through administrative supervision and field supervision. Supporting factors for implementation include inter-agency coordination through the Foreigner Supervision Team (TIMPORA), the implementation of Standard Operating Procedures (SOPs), the use of the Foreigner Reporting Application (APOA), operational support, and apparatus commitment. Meanwhile, the size of the work area, limited human resources, and limited budget are the main factors that hinder the implementation of supervision. This study confirms that the effectiveness of policy implementation is not only determined by the availability of resources, but also by the organization's ability to integrate various supporting factors and manage various limitations in implementing immigration supervision.